Comparison between the Outcomes of Standard Percutaneous Nephrolithotomy (S-PCNL) and Mini-Percutaneous Nephrolithotomy (M-PCNL) while Treating Renal Calculi - Muhammad Iqbal Nasim, Ayaz Ahmad Khan, Rajab Ali, Faraz Khalid, Safiullah Sohu, Zulfiqar Ahmed, Rashid Bin Hamid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In urology, the most common disorder is represented as renal stones. Renal stones have 10% of humans reporting complaints. Their recurrence rate is very high, exhibiting approximately 70 percent recurrence rate. There have been significant advancements made in the treatment of renal stones. PCNL can be used in situations where renal stones are between 10-20 millimeters in the lower pole of a kidney and larger than 20 millimeters. Objective: This study was performed to compare the outcomes of S-PCNL and M-PCNL while treating renal calculi. Study design: A randomized control trial Place and Duration This study was conducted in Karachi Institute of Kidney Diseases Karachi from February 2022 to February 2023 Methodology: There were a total of 50 people included in this research who were equally divided into 2 groups. All of the participants were having a single unilateral renal stone which was <3cm in size. All of the included people were aged 18 years or older. Each patient underwent a physical examination as well as laboratory investigations which included urine culture, CBC, liver function, urinalysis, coagulation profile, and kidney function. There were certain imaging studies that included pelvic and abdominal ultrasonography, kidney–urinary bladder X-ray (KUB), and either intravenous pyelography (IVP) or computed tomography urinary tract (CTUT). Results: There were 25 patients in each group; Group A (M-PCNL) and Group B (S-PCNL). There were 14 women and 11 men in group A. The mean age of group A was 36.9 years. There were 8 women and 17 men in group B. The average age of group B was 45.06 years. It was observed that the operation time for Group A was more than Group B. It is because stone fragmentation took longer as there was a need to break the stones into smaller pieces in group A. We also identified several complications. Conclusion: When compared to S-PCNL, M-PCNL offers longer operating times and achieves a greater stone-free rate, making it an excellent method for treating renal calculi. Keywords: mini-percutaneous nephrolithotomy, standard percutaneous nephrolithotomy, renal calculi, adults